2018
DOI: 10.3390/ijms19010138
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antithrombotic Activity of Peptides from Blue Mussel (Mytilus edulis) Protein

Abstract: The blue mussel (Mytilus edulis) reportedly contains many bioactive components of nutritional value. Water-, salt- and acid-soluble M. edulis protein fractions were obtained and the proteins were trypsinized. The resultant peptides were analyzed by ultra-performance liquid chromatography quadrupole time of flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS). 387 unique peptides were identified that matched 81 precursor proteins. Molecular mass distributions of the proteins and peptides were analyzed by sodium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…This result was only improved with Alcalase hydrolysis after 45 min (WGPH45A), which showed 25% thrombin-inhibitory activity. Although this value is not very high, similar results with Alcalase were reported in lupine protein hydrolysates [33], and in blue mussel proteins [39]. Taking together HD, ACE, and thrombin-inhibitory activity, we selected WGPH45A to analyze chemical and amino acidic composition and to evaluate biological activity in primary human monocytes.…”
Section: Resultssupporting
confidence: 61%
“…This result was only improved with Alcalase hydrolysis after 45 min (WGPH45A), which showed 25% thrombin-inhibitory activity. Although this value is not very high, similar results with Alcalase were reported in lupine protein hydrolysates [33], and in blue mussel proteins [39]. Taking together HD, ACE, and thrombin-inhibitory activity, we selected WGPH45A to analyze chemical and amino acidic composition and to evaluate biological activity in primary human monocytes.…”
Section: Resultssupporting
confidence: 61%
“…It has been shown that antithrombotic peptides contain three to 20 amino acids residues and the peptides possess a certain homology of the γ‐chain of fibrinogen as they can compete for the receptors of the thrombocytes and subsequently inhibiting the formation or aggregation of platelets (Cheng et al., 2019; Zhang, 2016). To date, most of the food‐derived antithrombotic peptides are mainly obtained by either enzymatic hydrolysis or gastrointestinal digestion of milk casein (Liu et al., 2019; Tu et al., 2017), blue mussel (Qiao et al., 2018), legume (Chalé et al., 2016), amaranth grain (Sabbione et al., 2016), and brewer's spent grain (Cian et al., 2018) proteins. As compared to enzymatic hydrolysis of proteins, there are only a few studies on fermentation of food proteins to obtain antithrombotic peptides and this provides a relatively interesting gap for researchers to explore.…”
Section: Structure–activity Relationship Of Bpsmentioning
confidence: 99%
“…For example, a high percentage of hydrophobic (aliphatic and aromatic) AA residues in antidiabetic peptides (Figure 4) [109][110][111] is necessary for inhibition of dipeptidyl peptidase IV, a key enzyme involved in degradation of incretins [110,112,113], and for recognition of receptors for glucagon-like peptides [114,115]. A high percentage of negatively charged AA residues (Figure 4) has been reported in antithrombotic peptides showing both direct thrombin inhibition [116,117] and inhibition of factors in intrinsic pathways [72,118]. A high frequency of positively charged AA residues in so-called cationic antimicrobial peptides ( Figure 4) [119][120][121] is proven to be necessary for interactions with anionic microbe membranes.…”
Section: Comparison Of the Structures Of Marine-sourced Peptides Withmentioning
confidence: 99%